Insolvency frameworks and private debt: An empirical investigation - Agostino Consolo; Federica Malfa; Beatrice Pierluigi (European Central Bank (ECB), 2018)
This paper presents new evidence on the importance of insolvency frameworks for private sector debt deleveraging and for the resolution of non-performing loans (NPL). We construct an aggregate insolvency framework index (IFI), which is used as explanatory variable in the empirical analysis. By means of panel estimates over 2003-2016, we show that OECD countries with better IFI deleverage faster and adjust their NPL levels more rapidly than countries with worse IFI. We also show that there is a strong correlation between the level of NPL and IFI, which appears to be state-dependent, i.e. in a situation of high unemployment relative to its historical average the NPL ratio is generally lower for a higher IFI. Finally, our results indicate that better insolvency frameworks lead to faster NPL reductions and to lower NPL increases during economic bad times.
Keywords: C23; E02; E05; O52; 330; private debt; non-performing loans; insolvency frameworks; panel estimates